Tools to Improve the Accuracy of Kidney Stone Sizing with Ultrasound - Dunmire, Barbrina (J Endourol, 2015)
Purpose: Ultrasound (US) overestimates stone size when compared with CT. The purpose of this work was to evaluate the overestimation of stone size with US in an in vitro water bath model and investigate methods to reduce overestimation. Materials and Methods: Ten human stones (3–12 mm) were measured using B-mode (brightness mode) US by a sonographer blinded to the true stone size. Images were captured and compared using both a commercial US machine and software-based research US device. Image gain was adjusted between moderate and high stone intensities, and the transducer-to-stone depth was varied from 6 to 10 cm. A computerized stone-sizing program was developed to outline the stone width based on a grayscale intensity threshold. Results: Overestimation with the commercial device increased with both gain and depth. Average overestimation at moderate and high gain was 1.9±0.8 and 2.1±0.9 mm, respectively (p=0.6). Overestimation increased an average of 22% with an every 2-cm increase in depth (p=0.02). Overestimation using the research device was 1.5±0.9 mm and did not vary with depth (p=0.28). Overestimation could be reduced to 0.02±1.1 mm (p<0.001) with the computerized stone-sizing program. However, a standardized threshold consistent across depth, system, or system settings could not be resolved. Conclusion: Stone size is consistently overestimated with US. Overestimation increased with increasing depth and gain using the commercial machine. Overestimation was reduced and did not vary with depth, using the software-based US device. The computerized stone-sizing program shows the potential to reduce overestimation by implementing a grayscale intensity threshold for defining the stone size. More work is needed to standardize the approach, but if successful, such an approach could significantly improve stone-sizing accuracy and lead to automation of stone sizing.